Isolated intramaxillary sinus cell causing long-standing facial pain: A case report. (August 2021) - Alromaih, Saud; Aloraini, Nouf; Alqaryan, Saleh; Sumaily, Ibrahim
Abstract: Introduction: Sinus pneumatization by definition is a cystic enlargement within the paranasal sinuses, and that expansion causes clinical symptoms. Importance: This case highlights the importance of identifying clinically significant sinus pneumatization and the significant role of surgical treatment. Case presentation: This case report describes a clinical presentation of intramaxillary sinus cell affecting the patient's quality of life. Despite the rare location of the cyst, it was diagnosed by computed tomography and managed by Functional Endoscopic Sinus surgery (FESS). Clinical discussion: This case discussion describes the nomenclature, classifications, location and the treatment of sinus pneumatic dilatations. Conclusion: Our case demonstrates the importance of managing the underlying cause of the patient symptoms by a thorough history and physical examination and it can be confirmed by imaging. Symptomatic maxillary air cysts, albeit controversial in its nomenclature and mechanism, should be addressed surgically as it carries high levels of success. Highlights: A unique symptom of intramaxillary sinus cell is facial pain, which is due to irritation of the trigeminal nerve. CT is considered the gold standard for diagnosis of this entity. This case highlights the importance of Surgery for severe symptoms with excellent prognosis and no reported recurrence.